2020
DOI: 10.1177/1082013220929150
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic, bacteriostatic effect of propolis and glycerol against Listeria monocytogenes in chocolate milk under refrigerated storage

Abstract: Propolis ethanolic extracts, with or without glycerol, were added into pasteurized, non-fat chocolate milk, which was artificially contaminated with Listeria monocytogenes. The addition of propolis ethanolic extracts dissolved into glycerol led to a definite anti-listerial effect in milk stored at 4 ℃, with both propolis concentrations tested (2 or 4 mg of dry propolis ethanolic extract per milliliter of chocolate milk) leading to inhibition of L. monocytogenes growth throughout 20 days of storage. The combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Moreover, the chocolate-flavored milk administered with glycerol and deodorized PE gained a considerable consumer acceptance rate without any negative comments or complaints. As a conclusion, propolis may exhibit an auspicious role in preserving dairy products [102]. El-Deeb [103] also suggested that propolis can effectively preserve dairy products such as milk and yogurt with improved shelf life.…”
Section: Dairymentioning
confidence: 95%
“…Moreover, the chocolate-flavored milk administered with glycerol and deodorized PE gained a considerable consumer acceptance rate without any negative comments or complaints. As a conclusion, propolis may exhibit an auspicious role in preserving dairy products [102]. El-Deeb [103] also suggested that propolis can effectively preserve dairy products such as milk and yogurt with improved shelf life.…”
Section: Dairymentioning
confidence: 95%
“…The phytochemical profile supports the wound-healing properties of the extract, such as glycerol and hexadecenoic acid. [ 16 17 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…Only a few works have reported the propolis bioeffect against Listeria . Almost all of them compared results between gram-positive and gram-negative bacteria [ 25 , 41 , 42 , 43 , 44 ] or studied Listeria in Ready-to-Eat (RTE) products, in addition to different conditions and components [ 11 , 16 , 31 , 45 , 46 , 47 , 48 ]. Previous studies against gram-positive microorganisms [ 49 ] with European propolis revealed MIC values ranging from 80 to 5000 µg/mL, while Polish propolis (400–8000 µg/mL) [ 41 , 42 ] revealed higher MIC values, referred to as L. monocytogenes (1560–6250 µg/mL).…”
Section: Discussionmentioning
confidence: 99%